Numerical Simulation of Artillery Chamber Explosion Using ALE Algorithm (Dandao Xuebao/Journal of Ballistics, 2023)
In order to investigate the possible causes of the tank chamber-explosion accident when a tank gun fires armor-piercing projectiles, the explosion of warhead charge caused by the early release of fuze was studied. The fluid-solid coupling method was adopted to simulate the process of tank chamber-explosion, and the mechanical characteristics were obtained, such as the stress variation. Firstly, the models of barrel, projectile shell, warhead charge and air domain were established by Solidworks, and the finite element mesh was divided by Hypermesh. Then, an arbitrary Lagrangian-Eulerian(ALE)algorithm was applied to solve the fluid-solid coupling problem between the explosive and the barrel in the LS-DYNA software, and the damage to the barrel caused by the explosion of the combatant charge triggered by the early fuse release was successfully simulated, and the fracture of barrel was basically reproduced. The results show that the stress on the inner barrel wall caused by the instantaneous detonation of the explosive can reach 29 GPa, and the change law of the inner wall pressure of the barrel shows a sudden rise and drop trend, which is closely related to the change law of the explosion shock wave energy produced by the explosive explosion. Furthermore, the produced fragments are uniform. Good agreements of the fracture characteristics have achieved between the numerical simulation and the actual situation. It can provide a useful reference for the further study of the actual situation, such as the damage effect of the explosion of warhead charge on the barrel caused by the early release of fuze.